Istikhdamu Wasilati Pop Up Book Bi Toriqoti As-Sam’iyah As-Safawiyah Li Tarqiyyati Saytoroti At-Tholibat ‘Ala Al-Mufrodati Al-Arabiyati - Santri Qarimah (Institut Agama Islam Darusssalam Blokagung, 2023)
In learning vocabulary, effective methods and media are needed, so that the learning process can take place well. Vocabulary is a very important element in learning and applying Arabic. The students' mastery of Arabic vocabulary at MTsN 1 Aceh Tenggara is not optimal. This can be seen based on the lack of students' understanding of the learning material contained in the book and when given practice there are still many students who do not know the meaning of the vocabulary contained in the questions given. The vocabulary used in the problem is the vocabulary they have learned. The purpose of this study was to find out how the use and effectiveness of Pop Up Book media with the Syam'iyyah Syafawiyyah method in improving students' Arabic vocabulary mastery at MTsN 1 Aceh Tenggara. This research uses the Quasi Experiment method. Researchers took a sample of 40 students in one class, namely class II-c. The instruments used are tests and observations. The results of the study were 1) The activities of teachers and students in the use of Pop Up Book media with the Syam'iyyah Syafawiyyah method at MTsN 1 Aceh Tenggara succeeded in increasing students' Arabic vocabulary mastery, this was based on the teacher's activity value of 84.61% in the category very good and the value of student activity is 92.30% with very good category. 2) The use of Pop Up Book media with the Syam'iyyah Syafawiyyah method at MTsN 1 Aceh Tenggara is effective in increasing students' Arabic vocabulary mastery. This is based on the results of the study that the t-test value is higher than the t-table value. Then the hypothesis of this study can be accepted.